Bridging Tradition and Tourism in Puri Saren Agung Ubud - Adnyawati, Ida Ayu Agung (Bali Tourism Journal, 2023)
Puri, as one of the cultural heritages, contains cultural elements worthy of conservation. In addition to culture, Puri carries a reputation and inherent authority, shaping the image of leaders in society. The ancient buildings with extraordinary architecture and carvings on each structure not only stand as witnesses to the kingdom's past but also function as a living museum. The artistic system within this cultural element is manifested by the shift in the function of Puri Saren Agung Ubud from a residence to a tourist destination packaged with cultural tourism. . Tjokorda Gde Agung Sukawati's visionary establishment of the Tedung Agung Studio in the 1980s has not only provided a space for children to learn dance and percussion but has also contributed to the preservation and evolution of traditional Balinese performing arts. The tourism experience of performing arts at Puri Saren Agung has further elevated the cultural significance of Ubud. Balinese art, with its dual functions of wali and balih-balihan, has become a captivating form of tourist performing art. From the classical Legong dance to other traditional performances, Puri Saren Agung Ubud has been a focal point for tourists seeking an authentic and immersive encounter with Balinese culture.